Evaluation of strength muscle recovery with isokinetic, squat jump and stiffness tests in athletes with ACL reconstruction: a case control study - Jacopetti, Marco; Pasquini, Andrea; Costantino, Cosimo (Acta Biomedica Atenei Parmensis, 2016)
BackgroundThe anterior cruciate ligament (ACL) rupture accounting for about 50% of all knee ligament injuries. The rehabilitation program requires a long time to rebuild muscle strength and to reestablish joint mobility and neuromuscular control. The purpose of the study is to evaluate the muscle strength recovery in athletes with ACL reconstruction. MethodsWe enrolled soccer atlethes, with isolated anterior cruciate ligament rupture treated with bone-patellar tendon-bone autograft artroscopic reconstruction. Each patients were evaluated comparing operated and controlateral limb by isokinetic test and triaxial accelerometer test. Isokinetic movements tested were knee flexion–extension with concentric-concentric contraction. Accelerometer test were Squat Jump Test (SJT)  and Stiffness Test (ST). Results17 subjects were selected, there was no significant difference in isokinetic quadriceps and hamstrings results in strength and endurance values. Parameters of ST were comparable between the operated and unoperated side. In SJT a significant statistical difference was in height of jump (p=0,02) no statistical difference was evidenced in the other measures.ConclusionCurrently complete recovery of symmetric explosive strength seems to be an important parameter for evaluating the performance after ACL reconstruction and the symmetry in test results jump could be associated with an adequate return to sports. In our study the explosive strenght is lower in the limb operated than the healthy one. Explosive strength recovery with pliometric training should be included in the post-surgical rehabilitation protocol and its measurement should be performed to assess the full recovery before the restart of sport activities.